2017
DOI: 10.1136/heartjnl-2017-311435
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of 1-year mortality in heart transplant recipients: a systematic review and meta-analysis

Abstract: High-quality and moderate-quality evidence demonstrates that recipient age, congenital aetiology, creatinine, pulsatile MCS, donor age and female donor to male recipient sex mismatch are associated with 1-year mortality post heart transplant. The results of this study should inform future guideline and predictive model development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 75 publications
6
31
1
Order By: Relevance
“…19 The ISHLT registry has shown that long-term survival postheart transplant is significantly lower in diabetic patients compared to those without diabetes (12% reduction in survival by 10-year post-transplant). 26 Despite this, our model's effect estimates for impact of BMI are similar, but more precise, than previously published work. There was an absolute 2% and 7% increase risk of 1-year mortality in those age 40-65 and >65, respectively, compared to those with a normal BMI and an age of 40-65.…”
Section: Primary Findingssupporting
confidence: 56%
See 1 more Smart Citation
“…19 The ISHLT registry has shown that long-term survival postheart transplant is significantly lower in diabetic patients compared to those without diabetes (12% reduction in survival by 10-year post-transplant). 26 Despite this, our model's effect estimates for impact of BMI are similar, but more precise, than previously published work. There was an absolute 2% and 7% increase risk of 1-year mortality in those age 40-65 and >65, respectively, compared to those with a normal BMI and an age of 40-65.…”
Section: Primary Findingssupporting
confidence: 56%
“…Hence, although we adjusted for the confounding and effect modifying impact of age and study source, we could not control for all other patient characteristics and comorbidities that may be modifying the risk of mortality. 26 Despite this, our model's effect estimates for impact of BMI are similar, but more precise, than previously published work. 2…”
Section: Limitationssupporting
confidence: 56%
“…In recipients with diabetes, there may be a combination of direct glucose-mediated endothelial damage, oxidative stress from superoxide overproduction and production of advanced glycation end-products, which may result in changes in endothelial permeability, excessive vascular protein deposition and altered blood flow (15). A recent metanalysis, diabetes mellitus was an independent predictor of 1-year mortality postheart transplant (16). They attributed this to the summative increased hazard for comorbidities of diabetes at time of transplant which was also noted by Russo et al (17).…”
Section: Risk Factorsmentioning
confidence: 99%
“…The Wald test was used to assess whether the hazard of mortality between days 361 and 365 differed significantly from the following 14 or 30 days, using the preceding 14 or 30 days before day 361 to define the baseline hazard 11 . Risk adjustment for one‐year post‐transplant survival and graft failure was performed using variables that have been previously demonstrated to be associated with post‐transplant survival 12‐14 . Candidate covariates were included in the multivariable model if they correlated with the outcome on univariate analysis in the timeframe in question (14 or 30 days) at a P ‐value <.05 (Table S1).…”
Section: Methodsmentioning
confidence: 99%